The Effectiveness of Comment Column on Facebook Group in Teaching Writing: Quantitative Method - Yulia Nugrahini (Darussalam English Journal (DEJ), 2021)
This article was a complete report of investigation on the effectiveness of coment column in facebook group to teach writing. Communicate using Facebook in international scope or globalization era needs English skill, especially in writing skill. Writing which is clearly and acceptably is needed when writing or given a comment. The Students must have good skill writing on English. The researcher was analized the score of pre test and posttest with used computing calculated with SPSS 21.0. The researcher analized used t-test. The researcher used t-test technique because in this research all the assumptions test are full filed. The result showed that the mean of the pre-test was 61.16 and mean of the post-test was 75.23. It means that the result from the post-test was higher than pre-test. Based on the result of output paired sample test shows the result of compare analysis with used T-test shows mean pre-test and post-test is 14.065. Standard deviation is 10.577 and mean standard error is 1.900, the lower different is 10.185, while upper different is 17.944. The result t- test is 7.404 with df 30 and significance 0.000. The t-count value is 7.404 is more than t- table value 2.042. So the Ho is rejected and Ha accepted because 7.404 > 2.042.The Average score of post-test is higher then the average of pre-test. It means that Facebook is an effective media in teaching writing procedure text.